Histological and molecular characterisation of hypotonia in adult Ts1Cje mouse model for down syndrome - Bala, Usman (2016)
Down syndrome (DS) is a genetic disorder caused by presence of extra copy of human chromosome 21 (Hsa21), a condition termed as trisomy 21. It is characterised by several number of clinical phenotypes such as intellectual disability, characteristic sets of facial features, cardiac defects and different systems anomalies. Motor dysfunction due to hypotonia is commonly seen in DS individuals and its etiology is yet unknown. Ts1Cje, which has a partial trisomy (Mmu16) synteny to Hsa21, is a mouse model for DS that is well reported to exhibit various typical neuropathologic features seen in DS individuals. However, hypotonia in Ts1Cje mouse has not been fully characterised. In this study, Ts1Cje mice was used to investigate the potential role of muscular and peripheral nervous systems defects in causing muscle weakness in DS individuals using molecular and histological approaches. Behavioural assessment of the motor performance showed that, the forelimb grip strength (automated grip test) was significantly (P<0.0001) greater in the wild type mice compared to the Ts1Cje mice, regardless of gender. The average survival time of the wild type mice was significantly (P<0.01) greater compared to those of the Ts1Cje mice (P<0.01). In addition, the cumulative number of falls in the Ts1Cje mice was significantly (P<0.0001) greater than those of their wild type littermates. The wild type mice performed significantly (P<0.01) better than the Ts1Cje mice in the latency to maintain a coordinated motor movement against the rotating rod (accelerated speed). Relative expression of both trisomic (Itsn1, Syjn1 and Rcan1) and the non-trisomic genes (Lamc1, Leprel1, Myl6b, Msn and Pgm5) showed no significant difference in both quadriceps and triceps of Ts1Cje mice as compared with the wild type. Expression of Myf5 was significantly (P<0.05) reduced in triceps of Ts1Cje mice while MyoD expression was significantly (P<0.05) increased in quadriceps of Ts1Cje mice as compared with wild type.